G6PD Polymorphisms and Hemolysis After Antimalarial Treatment With Low Single-Dose Primaquine: A Pooled Analysis of Six African Clinical Trials - Sepúlveda, Nuno; Grignard, Lynn; Curry, Jonathan; Mahey, Laleta; Bastiaens, Guido J. H.; Tiono, Alfred B.; Okebe, Joseph; Coulibaly, Sam A.; Gonçalves, Bronner P.; Affara, Muna; Ouédraogo, Alphonse; Bougouma, Edith C.; et al. (Frontiers in Genetics, 2021)
Primaquine (PQ) is an antimalarial drug with the potential to reduce malaria transmission due to its capacity to clear mature Plasmodium falciparum gametocytes in the human host. However, the large-scale roll-out of PQ has to be counterbalanced by the additional risk of drug-induced haemolysis in individuals suffering from Glucose-6-phospate dehydrogenase (G6PD) deficiency, a genetic condition determined by polymorphisms on the X-linked g6pd gene. Most studies on G6PD deficiency and PQ-associated haemolysis focused on the G6PD A- variant, a combination of the two single nucleotide changes G202A (rs1050828) and A376G (rs1050829), although other polymorphisms may play a role. In this study, we tested the association of 20 G6PD single nucleotide polymorphisms (SNPs) with haemolysis measured seven days after low single dose of PQ given at the dose of 0.1 to 0.75 mg/kg in 957 individuals from 6 previously published clinical trials investigating the safety and efficacy of this drug spanning 5 different African countries. After adjusting for inter-study effects, age, gender, baseline haemoglobin level, PQ dose, and parasitaemia at screening, our analysis showed putative association signals from the common G6PD mutation, A376G (-log10(p-value)=2.44) and two less-known SNP, rs2230037 (-log10(p-value)=2.60), and rs28470352 (-log10(p-value)=2.15); A376G and rs2230037 were in very strong linkage disequilibrium with each other (R2=0.978). However, when the effects of these SNPs were included in the same regression model, the subsequent associations were in the borderline of statistical significance. In conclusion, whilst a role for the A- variant is well established, we did not observe an important additional role for other G6PD polymorphisms in determining post treatment haemolysis in individuals treated with single low dose PQ.